Pressure ulcers in the aging population : a guide for clinicians - Compton, MD, Gregory A.; Thomas, MD, David R. (Aging Medicine, 2014)
Pressure Ulcers in the Aging Population: A Guide for Clinicians is a resource primarily aimed at physicians interested in the fundamentals of wound care. This book is written for geriatricians, internists, general practitioners, residents and fellows who treat older patients. Unlike other wound texts on the market, the book addresses the specific issues of wound prevention and management in older individuals. The text emphasizes proper documentation and elements of the team care process. There is up to date information on skin changes a the end of life and the concept of unavoidability. Chapters are written by experts in their fields and  include such evolving topics as deep tissue injury and the newer support surface technologies.